2021
DOI: 10.1111/1751-2980.13023
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐observer variability of experts and trainees for the diagnosis of reflux esophagitis: Comparison of linked color imaging, blue laser imaging, and white light imaging

Abstract: Objectives Diagnosis of reflux esophagitis according to the Los Angeles classification minimal change (LA‐M) has a low inter‐observer agreement. We aimed to investigate whether the inter‐observer agreement of reflux esophagitis was better when expert endoscopists read the endoscopic images, or when the linked color imaging (LCI) or blue laser imaging (BLI)‐bright mode was used. In addition, whether the inclusion of LA‐M in the definition of reflux esophagitis affected the consistency of the diagnosis was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(34 reference statements)
0
6
0
Order By: Relevance
“… 6 Since LCI enhances color contrast, it facilitates the identification of these typical endoscopic findings. 14 , 15 , 54 Moreover, under LCI, H. pylori -infected mucosa appeared deep red (crimson) in color, while H. pylori -negative mucosa (past infection or uninfected patients) could clearly be observed as apricot in color, which could be detected better because of distinctive color differences. 11 , 13 , 41 Dohi et al 11 showed that LCI improved the endoscopic diagnosis of active H. pylori infections, with 10% to 15% improvements in accuracy, sensitivity, and specificity over WLI.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Since LCI enhances color contrast, it facilitates the identification of these typical endoscopic findings. 14 , 15 , 54 Moreover, under LCI, H. pylori -infected mucosa appeared deep red (crimson) in color, while H. pylori -negative mucosa (past infection or uninfected patients) could clearly be observed as apricot in color, which could be detected better because of distinctive color differences. 11 , 13 , 41 Dohi et al 11 showed that LCI improved the endoscopic diagnosis of active H. pylori infections, with 10% to 15% improvements in accuracy, sensitivity, and specificity over WLI.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent Korean study showed that the interobserver agreement for the diagnosis of reflux esophagitis was very low for both experts and trainees, even after using BLI-brt or LCI. 17 This interobserver discrepancy was particularly prominent in grade LA-M reflux esophagitis. Therefore, further research is required to determine whether LCI is useful for the diagnosis of gastroesophageal reflux disease.…”
Section: Clinical Application In the Upper Gi Tractmentioning
confidence: 99%
“…BLI utilizes two monochromatic lasers (410 and 450 nm) to improve the visualization of the vascular microarchitecture of the mucosal surface. 27 This newer technology overcomes the limitation of a dark field view in previous narrowed-spectrum technologies. In contrast, LCI uses a specific color-enhancing technology that distinguishes color in red regions of mucosal blood vessels to improve the identification of red and discolored lesions based on differences in mucosal color.…”
Section: ) Blue Laser Imaging and Linked Color Imagingmentioning
confidence: 99%